## Trending News

# Solve for x: (3/2)x - (5/6) + x = (1/2)x + (2/3)?

I am so ? can someone explain to me how to figure out so i may get this and learn how to do it..

### 3 Answers

- 9 years agoFavorite Answer
Don't think too hard or intimidate yourself when it's not as bad as you think :)

The first thing I would do is immediately destroy the fractions!

Haha, not destroy but get rid of them.

You can do that by multiplying everything (yes, both sides) by the LCD which, in this case, is 6.

6(3/2x - 5/6 + x) = 6(1/2x + 2/3)

3(3x) - 5 + 6x = 3(1x) + 2(2)

9x - 5 + 6x = 3x + 4

Combine like terms like so:

15x - 5 = 3x + 4

Isolate the variable, x, like so:

15x - 3x - 5 = 4

12x = 4 + 5

12x = 9

x = 9/12

x = 3/4

If I were doing this for myself, I would've skipped half of these steps.

But since I don't know how much you understand, I just wrote it all out :)

I hope you understood that and good luck! ^^

Basic summary: 1. multiply both sides of the equation by the LCD

2. Combine like terms

3. Isolate the variable

Source(s): Algebra is my best and most favorite subject! :D - 9 years ago
1) add the x values together on the one side (so, 3/2 x and x)

2) get the x values on one side of the equation and the non-x on the other side. Do this by subtrating the x value from the one side and also from the other. Do the same basic thing on for the non-x values (you may need to add instead of subtract).

3) divide both sides by the number infront of the x

4) you should now have your answer

For this problem, you are going to need to get your denominators to be the same number. Find the lowest possible number that all denominators are divisible into. Multiply the numerator and denominator by the number needed to get the denominator to the common denominator. For example, if the common denominator is 6 (hint, hint), multiply the (3/2)x by (3/3).

- 9 years ago
first you multiply whole equation with 6, so you get rid of fractions.and you'll get:

9x - 5 + 6x = 3x + 4

now you transef unknowns to the left:

9x + 6x - 3x = 4 + 5

then cumulated them

12x = 9 / : 12

x = 9/12 = 3/4